Collagen type II is recognized by a pathogenic antibody through germline encoded structures. - Böiers, Ulrika; Lanig, Harald; Sehnert, Bettina; Holmdahl, Rikard; Burkhardt, Harald (European Journal of Immunology, 2008)
Collagen type II (CII) is a cartilage-specific target of pathologic humoral autoimmune responses in rheumatoid arthritis as well as in the collagen-induced arthritis model. The aim of the present study is to investigate the critical amino acid residues conferring CII epitope specificity of the prototypic arthritogenic murine mAb CIIC1. A homology model of the CIIC1 single-chain antibody fragment (CIIC1scFv) in complex with its triple helical epitope was established. In silico predictions based on extensive molecular dynamics simulations were experimentally tested by the recombinant expression and functional analysis of CIIC1scFv containing alanine replacements allowing the identification of crucial CII-binding sites in the CDR2 and CDR3 regions of both heavy and light chains. Since the conversion of the CIIC1scFv sequence into the respective germline at all 13 somatically mutated positions did not affect its CII binding, our data indicate that potentially harmful cartilage-specific humoral autoimmunity could be germline encoded. The molecular modeling further demonstrates that the rigid collagen triple helix restricts the likelihood of molecular interactions with the CDR regions of the antibody considerably compared with globular antigens. These sterical constraints provide an explanation as to why somatic mutations in the arthritogenic autoantibody have no obvious impact on CII recognition.